The Mediterranean, DASH, and MIND diets and the incident of hypertension over a median follow-up of 7.4 years in the Tehran Lipid and Glucose Study - Elham Razmpoosh; Nazanin Moslehi; Shima Abdollahi; Sepideh Soltani; Parvin Mirmiran; Fereidoun Azizi (BMC Public Health, 2022)
Abstract Background Despite the favorable effects of well-known dietary patterns in the treatment of hypertension (HTN), such as the Mediterranean (MED) and Dietary Approach to Stop Hypertension (DASH) diets, it is uncertain if adherence to these diets can reduce the risk of HTN, especially in non-Mediterranean populations. Moreover, none of the previous studies evaluated the association between the MED-DASH Intervention for Neurodegenerative Delay (MIND) diet adherence and the incidence of HTN. Therefore, we aimed to assess the association of adherence to these diets with the development of HTN in adults. Methods This prospective study included 2706 adults free of HTN who were selected from the Tehran Lipid and Glucose Study. The MED, DASH, and MIND diet scores were computed at baseline using dietary information collected with the food frequency questionnaire. Associations between the dietary indices and risk of HTN over a median follow-up of 7.4 years were examined using Cox proportional hazards regression analysis. Results The baseline mean age of participants was 37.9 ± 12.5 years (age range: 20–79 years), and 52.4% were women. During the 18262 person-years follow-up, 599 incidents of HTN were identified. There was no significant relationship between the dietary scores and the risk of HTN, either as continuous or categorical variables, even after excluding individuals with early/late HTN diagnosis, prehypertension, diabetes, or chronic kidney disease at baseline. A significant interaction was found between body mass index (BMI) and DASH (P-interaction < 0.001). Stratified analyses based on baseline BMI status revealed an inverse association between DASH and HTN risk in individuals with normal-weight (HR = 0.84, 95% CI = 0.71–0.98, P = 0.031), although this association did not reach statistical significance across the tertiles of DASH. Conclusions In this study, MED, DASH, and MIND showed no significant association with the occurrence of HTN in adults. Further prospective studies on diverse populations are required to assess whether adherence to the MED, DASH, and MIND diets is an effective strategy for reducing the occurrence HTN.